Clinical profile and Histopathological spectrum of Interface Dermatitis - Kriti, Kaira; Sheenam, Azad; S, Bisht Jeetendra; Rajnish, Kumar (Annals of Pathology and Laboratory Medicine, 2019)
Background- Interface Dermatitis is an etiologically diverse and poorly understood group of skin diseases characterized by pathology at the dermo-epidermal junction. The prototype disease is Lichen Planus but there are many other disease entities that exhibit Lichenoid tissue reaction / Interface changes. Aims- To study the clinical profile and Histopathological spectrum of Interface Dermatitis. Materials & Methods- This was a prospective study conducted at a tertiary care hospital over a period of eighteen months. A total of Ninety-eight cases clinically suggestive of diseases believed to show interface changes on histology were studied. Clinical details were recorded. Skin biopsies were taken from representative lesions. H&E stained sections were studied in detail for diagnosis and subtyping. Analysis was done in percentages and proportions. Results- Fifty-three cases (54%) showed IFD on histopathological examination. The most common age range was between 11-40 years and both the sexes were equally affected. Majority of the cases clinically presented as papules and plaques. The most common type of IFD were LP and its variants (52.1%). The most consistent microscopic findings were vacuolar degeneration of basal layer, pigment incontinence and inflammatory infiltrate around DEJ and blood vessels. Conclusions- IFD includes various diseases which have overlapping clinical as well as histopathological features. A detailed histopathological examination and correlation of the interface changes with clinical diagnosis is helpful in arriving at a definitive diagnosis which is essential for predicting the course of the disease and its optimal management.